AUDIOVISUAL MEDIA FOR THE DEVELOPMENT OF THE LISTENING SKILL IN THE ENGLISH LANGUAGE, IN THE STUDENTS OF THE EIGHTH GRADE "C" AT "TRES DE JULIO" HIGH SCHOOL, IN EL CARMEN-MANABÍ, PERIOD 2016-2017. - ZAMBRANO ÁLAVA, DIANA PAOLA (2016)
AUDIOVISUAL MEDIA ARE DIDACTIC ELEMENTS THAT INCLUDE BOTH IMAGES AND AUDIOS TO ACHIEVE AN EFFECTIVE LEARNING OF THE ENGLISH LANGUAGE, TAKING INTO ACCOUNT THAT THIS FORM PART OF LEARNING ENGLISH LANGUAGE AND THIS ABILITY IS VERY FUNDAMENTAL FOR LEARNING THIS SUBJECT. DUE TO IF PEOPLE DO NOT HAVE LISTENING SKILL; IT IS VERY HARD TO BE ABLE TO UNDERSTAND WHAT PEOPLE WANT TO TRANSMIT.